2015
DOI: 10.1016/j.agrformet.2015.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting growth and water use strategies in four co-occurring Mediterranean tree species revealed by concurrent measurements of sap flow and stem diameter variations

Abstract: 11Drought limits tree water use and growth of Mediterranean trees. However, growth and 12 water use strategies are rarely addressed simultaneously across species and drought 13 conditions. Here, we investigate the link between stem diameter variations and sap flow which allow them to cope with seasonal and interannual drought. 34A c c e p t e d m a n u s c r i p t 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
59
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 58 publications
9
59
1
7
Order By: Relevance
“…A previous study reported that Js for different species had a nonlinear negative relationship to ∆W when VPD > 0.5 kPa and solar radiation > 150 W·m −2 , and that it was related to soil water content [12]. However, we observed a strong nonlinear increase in Js with an increase in ∆W in Qinghai spruce, with Js subsequently gradually stabilizing when ∆W reached over 50 mm (Figure 3).…”
Section: Seasonal Course Of Sap Flow Density and Tree Water Deficitcontrasting
confidence: 43%
See 2 more Smart Citations
“…A previous study reported that Js for different species had a nonlinear negative relationship to ∆W when VPD > 0.5 kPa and solar radiation > 150 W·m −2 , and that it was related to soil water content [12]. However, we observed a strong nonlinear increase in Js with an increase in ∆W in Qinghai spruce, with Js subsequently gradually stabilizing when ∆W reached over 50 mm (Figure 3).…”
Section: Seasonal Course Of Sap Flow Density and Tree Water Deficitcontrasting
confidence: 43%
“…The significant positive nonlinear relationships between ∆W and R, and ∆W and VPD suggested that drought stress intensified with high solar radiation and vapor pressure deficit. High values of both factors increased water loss by transpiration, exacerbating drought stress [12,58,59]. Several studies reported that ∆W was significantly positively related to air temperature [18,19], which both influence transpiration.…”
Section: Environmental Control On Sap Flow Density and Tree Water Defmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many papers (e.g., Ehrenberger et al, ; Oberhuber, Hammerle, & Kofler, ; Oberhuber, Kofler, Schuster, & Wieser, ; Sánchez‐Costa, Poyatos, & Sabaté, ) deal with tree water status (or tree water deficit, Δ W ) calculated throughout the daily courses, we focused on extracted morning Δ W , which seems to be more connected to soil water availability represented by Ψ . When the soil is not fully hydrated, soil and stem water potentials are lower, and water storage pools are no longer replenished overnight (Steppe et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Sap flow is higher in winter than in summer, but trees do not allocate carbon to aboveground growth in winter (Sánchez-Costa et al 2015). Thus, carbon assimilated during winter is likely to be directed to other functions, such as defence or cold hardening.…”
Section: Trends Of Crown Defoliation and Their Relationship With Droumentioning
confidence: 99%